CDC's National Violent Death Reporting System: background and methodology. Issue 1 (3rd February 2004) - Paulozzi, L J; Mercy, J; Frazier, L; Annest, J L
Abstract : Objectives: This paper describes a new surveillance system called the National Violent Death Reporting System (NVDRS), initiated by the United States Centers for Disease Control and Prevention. NVDRS's mission is the collection of detailed, timely information on all violent deaths. Design: NVDRS is a population based, active surveillance system designed to obtain a complete census of all resident and occurrent violent deaths. Each state collects information on its own deaths from death certificates, medical examiner/coroner files, law enforcement records, and crime laboratories. Deaths occurring in the same incident are linked. Over 270 data elements can be collected on each incident. Setting: The 13 state health departments of Alaska, Colorado, Georgia, Maryland, Massachusetts, New Jersey, North Carolina, Oklahoma, Oregon, Rhode Island, South Carolina, Virginia, and Wisconsin. Subjects: Cases consist of violent deaths from suicide, homicide, undetermined intent, legal intervention, and unintentional firearm injury. Information is collected on suspects as well as victims. Interventions: None. Outcome measures: The quality of surveillance will be measured in terms of its acceptability, accuracy, sensitivity, timeliness, utility, and cost. Results: The system has just been started. There are no results as yet. Conclusions: NVDRS has achieved enough support to begin data collection efforts in selected states. This system will need to overcome the significant barriers to such a large data collection effort. Its success depends on the use of its data to inform and assess violence prevention efforts. If successful, it will open a new chapter in the use of empirical information to guide public policy around violence in the United States.